Logical thinking skills and science process skills of Secondary three students in neighbourhood schools of Singapore - Salinah Mohd Yunos. (2008)
The purposes of the research were i) to perform a baseline study in Singapore for logical thinking skills and science process skills, ii) to study the relationship between logical thinking skills and science process skills in the Singapore context.